Pizza, beer and kittens: Negotiating cultural trauma discourses on Twitter in the wake of the 2017 Stockholm attack. (November 2018) - Eriksson, Moa
The overarching aim of this study is to analyse how social media communication can impact the formation of cultural trauma discourses in the aftermath of disruptive societal events. The article focuses on how the hashtag #openstockholm was used on Twitter for support, sharing and cooperation after the Stockholm lorry attack in 2017. Much of the content posted with this hashtag had a light-hearted tone, flouting the conventional trauma discourses of grief and sorrow in a way that was surprising, and perhaps even provocative, to some. A thematic analysis of tweets shows the different uses of the hashtag over time, as well as distinguishes two conflicting discourses that either downplayed or amplified the cultural trauma narrative. The study shows that the responses to traumatic events may depend on a culturally specific logic of collective action frames which implies the need for contextual understandings of how cultural trauma discourses are negotiated.